Plasma Hsp72 (HSPA1A) and Hsp27 (HSPB1) expression under heat stress: influence of exercise intensity - Périard, Julien D. (Springer Netherlands, 2012)
Extracellular heat-shock protein 72 (eHsp72) expression during exercise-heat stress is suggested to increase with the level of hyperthermia attained, independent of the rate of heat storage. This study examined the influence of exercise at various intensities to elucidate this relationship, and investigated the association between eHsp72 and eHsp27. Sixteen male subjects cycled to exhaustion at 60% and 75% of maximal oxygen uptake in hot conditions (40°C, 50% RH). Core temperature, heart rate, oxidative stress, and blood lactate and glucose levels were measured to determine the predictor variables associated with eHsp expression. At exhaustion, heart rate exceeded 96% of maximum in both conditions. Core temperature reached 39.7°C in the 60% trial (58.9 min) and 39.0°C in the 75% trial (27.2 min) (P < 0.001). The rate of rise in core temperature was 2.1°C h(−1) greater in the 75% trial than in the 60% trial (P < 0.001). A significant increase and correlation was observed between eHsp72 and eHsp27 concentrations at exhaustion (P < 0.005). eHsp72 was highly correlated with the core temperature attained (60% trial) and the rate of increase in core temperature (75% trial; P < 0.05). However, no common predictor variable was associated with the expression of both eHsps. The similarity in expression of eHsp72 and eHsp27 during moderate- and high-intensity exercise may relate to the duration (i.e., core temperature attained) and intensity (i.e., rate of increase in core temperature) of exercise. Thus, the immuno-inflammatory release of eHsp72 and eHsp27 in response to exercise in the heat may be duration and intensity dependent.